Revision of the genus Platyscelis Latreille, 1818 from China (Coleoptera: Tenebrionidae: Platyscelidini) - Bai, Xing-Long; Ren, Guo-Dong (Zootaxa, 2019)
The genus Platyscelis Latreille, 1818 (Coleoptera: Tenebrionidae: Platyscelidini) from China is revised. Sixteen valid species (subspecies) are recognized in this study, including three new ones: P. (s. str.) acutipenis sp. nov. from Gansu and Ningxia, P. (s. str.) densipunctata sp. nov. from Gansu, and P. (s. str.) helanensis sp. nov. from Inner Mongolia and Ningxia. A synonymy between P. (s. str.) brevis Baudi di Selve, 1876 and P. ballioni Reitter, 1889 is proposed based on the examination of type and additional specimens. Lectotypes are designated for P. hauseri Reitter, 1899, P. gebieni Schuster, 1915, P. (s. str.) angusticollis Kaszab, 1940, P. (s. str.) licenti Kaszab, 1940, P. (s. str.) platytarsis Kaszab, 1940 and P. (s. str.) suiyuana Kaszab, 1940. Furthermore, new distribution records, images of adults and male aedeagus, and a key to Chinese species are presented.